2017
DOI: 10.1002/cae.21836
|View full text |Cite
|
Sign up to set email alerts
|

Increasing middle school students’ awareness and interest in manufacturing through digital game‐based learning (DGBL)

Abstract: The change of the societal appeal of manufacturing among younger generations is a key element in order to address the talent shortage that is currently affecting the sector. In order to pursue this objective, the use of interactive learning environments such as digital games (DGs) can play an important role. Therefore, this paper presents the results of an exploratory study aimed at understanding the impact of digital game‐based learning (DGBL) on the awareness and interest of middle school students in manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…GBL is thought to be an effective tool that can promote learning experiences (Connolly, Boyle, MacArthur, Hainey, & Boyle, ) and motivation (Hung, Sun, & Liu, ; Papastergiou, ; Perini, Maria, Fradinho, & Manuel, ). Kebritchi and Hirumi () identified the following five reasons for applying GBL to instruction: (a) GBL emphasizes peers' interactions, (b) GBL creates personal motivation and satisfaction, (c) GBL accommodates multiple learning styles, (d) GBL reinforces mastery of skills, and (e) GBL provides a collaborative and decision‐making context.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…GBL is thought to be an effective tool that can promote learning experiences (Connolly, Boyle, MacArthur, Hainey, & Boyle, ) and motivation (Hung, Sun, & Liu, ; Papastergiou, ; Perini, Maria, Fradinho, & Manuel, ). Kebritchi and Hirumi () identified the following five reasons for applying GBL to instruction: (a) GBL emphasizes peers' interactions, (b) GBL creates personal motivation and satisfaction, (c) GBL accommodates multiple learning styles, (d) GBL reinforces mastery of skills, and (e) GBL provides a collaborative and decision‐making context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furió, González‐Gancedo, Juan, Seguí, and Rando () indicated that GBL could provide multiple benefits to teachers in terms of helping them to develop appropriate strategies for achieving a number of instructional purposes. When learning through games, students typically take greater interest in and have more opportunities for discovering, talking, exploring, and questioning (Perini et al, ; Yang, ). However, the use of GBL does not guarantee that learners will consistently achieve better learning results because it is not possible to identify a clear causal relationship between students' gameplay experiences and academic performance (Byun & Joung, ; Meluso et al, ; Wrzesien & Raya, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this project focused on Chemistry literacy, and it was coded in the frame of analysis, Content-Knowledge. Nodal points awareness of complexity [29], Eco-Factory [30], and BINKA curriculum (Mindfulness) [31] Sustainability Education in an Environment of Diversity (or SEEDs) module [32], value meaning making [33] Ecolife workshop [34], sustainable camp in Utah [35] and The Going Green! Middle Schoolers Out to Save the World project (MSOSW) project [32] Skills Geospatial thinking…”
Section: Table 4 Domains and Excerpt Examples For The Frame Of Analysmentioning
confidence: 99%
“…For instance, for the Level 2 Context: student community schools/county state, we found that students explored concepts such as sustainable energy supplies, water quality and purification [51] within their communities. In contrast, the resources classification for Level 3 Global context-Countries, students explored water and energy resources in a global perspective [28]- [54], [55], [30]. In Level 4 Planetary boundaries, the students explore concepts in a broader perspective, in some cases in the level of a planet [49] [50].…”
Section: Informed-decisions Makingmentioning
confidence: 99%
See 1 more Smart Citation